Analisis Penerapan Pajak Restoran Pada Rumah Makan Ayam Goreng Fatmawati Di Makassar - Indri Amalia; Nurul Afifah; Djusdil Akrim (JURNAL PABEAN : PERPAJAKAN BISNIS EKONOMI AKUNTANSI MANAJEMEN, 2021)
development and increasing welfare. The city government collects several types of taxes including restaurant tax. This study aims to determine the application of restaurant tax at the Fatmawati Fried Chicken Restaurant. The method used in this research is qualitative research, the restaurant tax collection procedure carried out by the restaurant is in accordance with the Regional Regulation by using a tariff of ten percent of the price of food and beverages as the basis for imposition of taxes (DPP). Deposit is applied by using Regional Tax Payment (SSPD) which is deposited together with tax that has been collected. The application of Restaurant Tax Reporting is carried out using a Regional Tax Return (SPTPD) which is carried out at the Makassar City Bapenda no later than the 20th of the following month. Based on the data received by the researchers, from July to December 2019 it can be concluded that the Fatmawati Fried Chicken Restaurant is late every month in depositing its taxes from this study. 2018 concerning Restaurant Tax. Keywords: Restaurant Tax, Collection, Deposit and Reporting, Regional Regulation Number 2 of 2018